Pemodelan Augmented Reality Edukasi Tata Surya Menggunakan Metode Marker Based Tracking dan Uat - Dewi Susanti Hulu; Agusta Pratama Wibawa (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
The development of interactive education as learning in education generally has several influencing factors, such as teachers who teach experiencing difficulties in keeping up with developments in information technology, learning media support tools for teaching in institutions are still limited in their use, only a few teachers use information technology in learning media because they have the knowledge to apply it to the teaching process, then from the problems that occur, the objectives include this research, designing an application interface display concept as an innovation in the use of learning technology according to needs, then creating an augmented reality learning application about the solar system according to the design created, after knowing the objectives What will be carried out in this research is implementing the use of an augmented reality application for the solar system using the marker based tracking method, where there is 3D object scanning of each planetary object in the solar system, while testing the application on 50 students of SDN Kebon Jeruk 15 Pagi, both classes VI A and B uses the user acceptance model (UAT), from the explanation explained if it is analyzed it produces an augmented reality application that has been created regarding the Android-based solar system so that it can be concluded that the testing process can be categorized as good or not in terms of AR applications and 3D object marker flashcards for students at school.